Ethical Business Practices And AI-Driven Marketing For Product Branding In MSMEs - Selvi Agustina (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This research aims to investigate the integration of ethical business practices and AI-driven marketing strategies for product branding within Micro, Small, and Medium Enterprises (MSMEs). The study adopts a qualitative approach, utilizing semi-structured interviews and content analysis. A purposive sampling technique will be employed to select participants from diverse MSMEs. Data will be analyzed thematically to identify patterns and insights regarding the implementation and impact of ethical practices and AI-driven marketing on branding strategies. The findings are expected to provide nuanced understandings of the challenges, opportunities, and outcomes associated with integrating ethical principles and AI technologies in MSMEs' branding endeavors, offering valuable insights for both practitioners and scholars in the field of marketing and business ethics.